2020
DOI: 10.3390/cancers12102848
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin and Ubiquitin-Like Proteins Are Essential Regulators of DNA Damage Bypass

Abstract: Many endogenous and exogenous factors can induce genomic instability in human cells, in the form of DNA damage and mutations, that predispose them to cancer development. Normal cells rely on DNA damage bypass pathways such as translesion synthesis (TLS) and template switching (TS) to replicate past lesions that might otherwise result in prolonged replication stress and lethal double-strand breaks (DSBs). However, due to the lower fidelity of the specialized polymerases involved in TLS, the activation and suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 140 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…In standard-of-care cancer therapies that involve platinum-based clinical agents, e.g., cisplatin or oxaliplatin, POLH can also bypass platinum-DNA adducts, negating the benefits of the treatment and enabling drug resistance [19][20][21][22][23][24][25][26][27]. Moreover, POLH has been implicated in resistance to nucleoside analogs, such as gemcitabine and cytarabine [28], and other studies suggest that POLH plays an important role in oxidative stress resistance, likely by carrying out the TLS [29,30] of bulky oxidative base lesions, such as cyclopurines [31][32][33]. Beyond its canonical TLS functions, recent studies found that POLH is important for resistance against the chemotherapeutic alkylating agent, temozolomide (TMZ), seemingly via a TLS-independent mechanism [34].…”
Section: Polh Backgroundmentioning
confidence: 99%
“…In standard-of-care cancer therapies that involve platinum-based clinical agents, e.g., cisplatin or oxaliplatin, POLH can also bypass platinum-DNA adducts, negating the benefits of the treatment and enabling drug resistance [19][20][21][22][23][24][25][26][27]. Moreover, POLH has been implicated in resistance to nucleoside analogs, such as gemcitabine and cytarabine [28], and other studies suggest that POLH plays an important role in oxidative stress resistance, likely by carrying out the TLS [29,30] of bulky oxidative base lesions, such as cyclopurines [31][32][33]. Beyond its canonical TLS functions, recent studies found that POLH is important for resistance against the chemotherapeutic alkylating agent, temozolomide (TMZ), seemingly via a TLS-independent mechanism [34].…”
Section: Polh Backgroundmentioning
confidence: 99%
“…Further polyubiquitination of this ubiquitin moiety on PCNA is also possible and initiates an alternative pathway of template switching (reviewed in ( Branzei and Szakal, 2017 , 2016 ; Prado, 2018 ). Polyubiquitination of PCNA involves the heterodimeric E2 complex Mms2-Ubc13 and the E3 proteins HLTF or SHPRH; the polyubiquitin chain forms on ubiquitin’s K63 residue rather than K48, the former type triggering template switching and the latter recognition and degradation by the proteasome (reviewed in Gallo and Brown, 2019 ; Kanao and Masutani, 2017 ; Leung et al., 2018 ; Ripley et al., 2020 ; Wilkinson et al., 2020 ). What determines the “decision” of whether PCNA is simply monoubiquitinated or further polyubiquitinated with activation of TLS or template switching, respectively, is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to UV-induced DNA damage, POLH has been shown to bypass cisplatin adducts, as well as oxaliplatin adducts (8)(9)(10)(11)(12)(13)(14). Additional studies suggest that POLH may also play an important role in oxidative stress resistance, likely by carrying out translesion synthesis (TLS) (15,16) of bulky oxidative base lesions, such as cyclopurines (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%